Feeding Problems in Children with Autism Spectrum Disorders - Cherif, Leila; Boudabous, Jaweher; Khemekhem, Khaoula; Mkawer, Salma; Ayadi, Héla; Moalla, Yousr (Journal of Family Medicine, 2018)
Background: Feeding problems are common in autism. Parents are frequently worried about the health status of their children, which may be threatened by some consequent nutritional deficiencies. Despite this, feeding behaviours remain little explored by clinicians working with children with autism spectrum disorders and researches are lacking especially in Tunisia. Aims: To evaluate the frequency and the types of feeding problems in children with autism spectrum disorders. Settings and Design: A comparison was made between 57 children with autism spectrum disorders and 57 control groups regarding the feeding problems. Parents completed the children’s eating behavior inventory (CEBI). Autism severity is evaluated using the Childhood Autism Rating Scale. The SPSS statistical package, version 20.0 was used. Results: According to the CEBI, children with autism spectrum disorders showed more feeding problems than the control group (82.4% versus 56.1%, p=0.002). In fact, the parents of these children observed more pica habits on their children compared to the control group (p=0.000). They also observed more selectivity for starchy foods compared to the control group (p=0.000). The more the autistic symptoms were severe, the more children exhibited feeding problems (p=0.02). Conclusions: Our findings suggest that feeding problems are more common in children with autism. Clinical implications trigger the need for clinicians to provide the necessary assessment and treatment.
Keywords: autism; feeding behavior; children; food selection